Female Headteachers’ Transformative Practices for School Improvement in Kailali District - Saud, Hark Bahadur (Journal of Durgalaxmi, 2024)
Headteachers play a pivotal role in managing both the academic and administrative activities in schools, which is crucial for raising academic standards and improving educational outcomes. This study aims to explore the transformative leadership practices of female head teachers in the Kailali district of Nepal, particularly focusing on how they contribute to overall school improvement. The research was guided by an interpretive paradigm, acknowledging that multiple interpretations exist, shaped by context. This approach allowed for an exploration of the lived experiences, stories, and narratives of four female secondary school head teachers in the Kailali district, located in the lowland region of Nepal's Far Western province. The study employed narrative inquiry as a research method and used participants' stories as the primary data source. The findings, grounded in transformational leadership theory, suggest that these female head teachers are highly dedicated, committed, and confident in their ability to bring about significant changes in their schools. They actively encourage collaboration among department heads and teachers, promote the sharing of ideas, and engage with local community stakeholders, government, and non-state sectors to enhance their influence. Additionally, they utilize public platforms to bolster their leadership impact. The research highlights the importance of recognizing individuals' interests and strengths, assigning additional roles, and creating leadership opportunities. By providing resources, encouragement, and support, these head teachers foster sustained motivation among their staff. Moreover, they emphasize the need for training and professional development for teachers and administrative staff, leveraging technology to intellectually stimulate their teams.